Penerapan Model Pembelajaran Jigsaw Dengan Pendekatan Scientific Untuk Meningkatkan Hasil Belajar IPA - Ai Rusmiati; Surti Kurniasih; Nandang Hidayat (Pedagogia: Jurnal Ilmiah Pendidikan, 2015)
The research is a classroom action which is aimed at improving the learning outcome of natural science subject with the research subjects of 42 students at class VIII-5. The research was done in two cycles. Each cycle has 4 steps, namely: planning, doing, observing, and reflecting. At the end of each cycle, there was a test with the instruments that had been validated and tested for its reliability. Based on the result of reflection of the previous year, the average score was 66,12 and the percentage of students achieving the score above the minimum was 45,24%. When Jigsaw model combined with the scientific approach were conducted, the average score and the percentage improved. At the first cycle, the average score of IPA subject with the aspect of cognitive reached 70,56 and the percentage of students getting the score above the minimum was 64,29% and at the second cycle, it improved into 75,32 and the achieving percentage was 80,95%. The learning result from the aspect of attitude was 61,90% the students got good category for the first cycle, while in the second cycle, the percentage of students getting good category 76,19%. The learning outcome from the aspect of skill reached 57,14% of students getting high category was. Second treatment at the first cycle was 61,90%, first treatment in the second cycle was 66,67%, second treatment in the second cycle was 76,19 and the third treatment in the second cycle was 78,57%, the students got high category. This result shows that the implementation of Jigsaw model with scientific approach can improve students’ learning outcome of natural science class at class VIII-5 SMP Negeri 2 Cicurug